2015
DOI: 10.1111/risa.12343
|View full text |Cite
|
Sign up to set email alerts
|

How Anxiety Leads to Suboptimal Decisions Under Risky Choice Situations

Abstract: The current research proposes that situationally activated anxiety--whether incidental or integral-impairs decision making. In particular, we theorize that anxiety drives decisionmakers to more heavily emphasize subjective anecdotal information in their decision making, at the expense of more factual statistical information--a deleterious heuristic called the anecdotal bias. Four studies provide consistent support for this assertion. Studies 1A and 1B feature field experiments that demonstrate the role of inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Study 2 tested the effect of task type in the context of online reviews where people typically receive two types of information: an aggregate rating based on ratings from multiple users, and a sample of individual ratings and verbal reviews. Prior research has shown that people often discount aggregate numerical information in the presence of anecdotal evidence (Alter et al 2007;Tversky and Kahneman 1973;Yang, Saini, and Freling 2015). For example, when asked to evaluate the probability that Jack is an engineer, people may ignore the proportion of engineers in the sample and rely on Jack's verbal description instead, a decision bias often referred to as base rate neglect (Tversky and Kahneman 1973).…”
Section: Study 2: Rejection and The Role Of Aggregate Vs Anecdotal Ementioning
confidence: 99%
See 1 more Smart Citation
“…Study 2 tested the effect of task type in the context of online reviews where people typically receive two types of information: an aggregate rating based on ratings from multiple users, and a sample of individual ratings and verbal reviews. Prior research has shown that people often discount aggregate numerical information in the presence of anecdotal evidence (Alter et al 2007;Tversky and Kahneman 1973;Yang, Saini, and Freling 2015). For example, when asked to evaluate the probability that Jack is an engineer, people may ignore the proportion of engineers in the sample and rely on Jack's verbal description instead, a decision bias often referred to as base rate neglect (Tversky and Kahneman 1973).…”
Section: Study 2: Rejection and The Role Of Aggregate Vs Anecdotal Ementioning
confidence: 99%
“…For example, when asked to evaluate the probability that Jack is an engineer, people may ignore the proportion of engineers in the sample and rely on Jack's verbal description instead, a decision bias often referred to as base rate neglect (Tversky and Kahneman 1973). Similarly, when choosing between two insurance plans offered by companies A and B, people can disregard the aggregate satisfaction ratings of the two companies, and instead rely on the personal experience of a specific consumer when making their decisions (Yang, et al 2015). Importantly, the tendency to discount aggregate numerical information in the face of anecdotal evidence is reduced under more deliberative processing (Alter et al 2007;Yang, et al 2015).…”
Section: Study 2: Rejection and The Role Of Aggregate Vs Anecdotal Ementioning
confidence: 99%
“…First, emotions underlie many aspects of risk perception . For example, anxious individuals appear to rely more on anecdotal evidence when making decisions, or choose more certain, apparently less risky options than angry individuals . Emotions expressed on social media also appear to influence the trustworthiness and usefulness of the messages .…”
Section: Introductionmentioning
confidence: 99%
“…All these changes in the mood of a community directly affect reliability of the community to recover to a normal state. In fact, several studies correlate disruptive events with long‐lasting effects on mood states …”
Section: Introductionmentioning
confidence: 99%